Electrochemical Activation Process for Treating High Strength Waste - Yap, Siew Yein (2001)
Electrochemical Activation Process (ECA) is a method whereby electrical current is introduced to induce a chemical reaction in water containing natural salts. As a result, this process will produce a substantial electrical potential difference, leading to the generation of anolyte and catholyte. The anolyte generated by the STEL®-ECA unit system were found to contain Cl2, Cl, HClO, HCl, Cl02, O2, 03, and H2O2. As for catholyte, analyses using the ICP and IR spectroscopy showed that it contains the hydroxides of sodium, potassium, magnesium and calcium. Besides, kinetic studies on the decomposition of the components in anolyte were also studied. Both activated solutions, anolyte and catholyte were used to treat passivation waste and landfill leachate. The studies include using anolyte and catholyte in COD reduction, the effect of contact time (of anolyte and the waste) on COD reduction, kinetics of the reaction between anolyte and the waste, using of catholyte in coagulation and flocculation, biodegradability of the waste after treatment and others. Finally, a case study was carried out to investigate the possibility of using anolyte in combination with other treatment method for example, aerobic, anaerobic, sedimentation and absorption to treat chemical waste. The physical-chemical-biological treatment reactor designed for the treatment of chemical waste was closely monitored for 143 days on its COD, BOD and biodegradability. F or passivation waste, COD removal was 70% using anolyte for at least 24 hours of contact time. High efficiency on the formation and settling of floc were observed when catholyte is used together with alum and anionic polymer. In addition, the non-readily biodegradable waste was transformed to a more readily biodegradable waste after at least a 24 hours reaction with the activated solutions. As for leachate, anolyte showed good reduction in COD and ammoniacal nitrogen, whereas catholyte showed good reduction in ferum and zinc. Finally, data obtained from the case study showed that anolyte is able to convert a non-readily biodegradable waste to a more readily biodegradable waste.